Question

solve using the LaPlace transform:

y'' - 6y' - 16y = 8e^{t}

y(0) = 2

y'(0) = -1

Answer #1

Use the Laplace transform to solve the following initial value
problem:
y′′ + 8y ′+ 16y = 0
y(0) = −3 , y′(0) = −3
First, using Y for the Laplace transform of y(t)y, i.e., Y=L{y(t)},
find the equation you get by taking the Laplace transform of the
differential equation
__________________________ = 0
Now solve for Y(s) = ______________________________ and write the
above answer in its partial fraction decomposition, Y(s) = A /
(s+a) + B / ((s+a)^2)
Y(s) =...

use
the laplace transform to solve the following equation
y”-6y’+9y = (t^2)(e^(3t))
y(0)=2
y’(0)=17

Use the Laplace Transform to solve the following initial value
problem:
11. y′′ −y′ −6y={0 for0<t<2; e^t for t>2}, y(0)=3,
y′(0)=4

Use the laplace transform to solve for the initial
value problem:
y''+6y'+25y=delta(t-7)
y(0)=0 y'(0)=0

Use the Laplace transform to solve the given initial-value
problem.
y'' + 6y' +
34y = δ(t −
π) + δ(t −
7π), y(0) =
1, y'(0) = 0

Use the Laplace transform to solve the given initial-value
problem.
y'' − 6y' + 13y = 0, y(0) = 0, y'(0) =
−5
#14 7.3
y(t) ?
please show work and circle the answer

solve the following DE using laplace transform
y"+4y'+4y=0; y(0)=-2, y'(0)=9

solve using the laplace transform y''-2y'+y=e^-t , y(0)=0 ,
y'(0)=1

y^''-y^'-2y= e^t , y(0)=0 and y^'(0)=1
Solve by using laplace transform

using laplace transform, solve:
y''+4y=8cos2t; y(0)=0, y'(0)=4

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 31 minutes ago

asked 36 minutes ago

asked 57 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago

asked 3 hours ago

asked 3 hours ago